Representation of Muslim Women in Youtube Media: Laïcité Policy and Human Rights in France - Husnah, Nurul; Ulinnuha, Roma (Journal of Law, Politic and Humanities, 2024)
This study focuses on the representation of Muslim women in France within France24's YouTube content, particularly concerning Laïcité policy and human rights issues. It analyzes perspectives from politicians, historians, and members of the Muslim community to understand the impact of Laïcité on Muslim women's rights. Muslim women in France face tensions between secular values and their religious identities, often resulting in feelings of isolation and marginalization. The research employs the Netnography method with a content analysis approach to explore this topic on France24's YouTube channel. Findings indicate that France24 plays a central role in presenting diverse perspectives and complex situations. The coverage highlights the effects of Laïcité on Muslim women's individual rights, emphasizing potential limitations on their religious identities. The public's understanding of Laïcité and its influence on Muslim women is analyzed based on the presented content. This provides a comprehensive depiction of how views on Laïcité policy are reflected in media platforms and how it affects the perception and individual human rights, particularly for Muslim women in France.